Structural Abnormalities in Patients with Insular/Peri-insular Epilepsy: Spectrum, Frequency, and Pharmacoresistance - Chevrier, M.-C.; Bard, C.; Guilbert, F.; Nguyen, D.K. (American Journal of Neuroradiology, 2013)
SUMMARY: Between 2002 and 2010, a total of 48 patients were seen at our epilepsy clinic with insular/peri-insular cortex epilepsy. Review of their MR imaging scans revealed a neoplastic lesion in 27% of patients, a malformation of cortical development in 21%, a vascular malformation in 19%, and atrophy/gliosis from an acquired insult in 17%. MR imaging results were normal in 4 patients. Other miscellaneous findings included a case of Rasmussen encephalitis, a nonspecific insular millimetric T2 signal abnormality, a neuroepithelial cyst, and hippocampal sclerosis without MR imaging evidence of dual insular pathologic features (despite depth electrode–proven insular seizures). Refractoriness to antiepileptic drug treatment was present in 56% of patients: 100% for patients with malformations of cortical development (1.0; 95% CI, 0.72–1.0), 50.0% (0.5; 95% CI, 0.21–0.78) in the presence of atrophy/gliosis from acquired insults, 39% (0.39; 95% CI, 0.14–0.68) for neoplastic lesions, and 22.2% (0.22; 95% CI, 0.06–0.55) for vascular malformations. IPICEinsular/peri-insular cortex epilepsyMCDmalformation of cortical development